2012
DOI: 10.1007/s00059-012-3648-3
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 and E-selectin in acute coronary syndromes and stable angina pectoris

Abstract: In the current study, inflammation as measured by IL-6 and E-selectin was not found to play an important role in progression of ischemic heart disease from stable angina to unstable angina or myocardial infarction, which is contrary to previous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…20 This finding was consistent with those of Sarrafzadegan et al, Tang et al and Caselli et al who too had reported higher concentrations of IL-6 in patients with stable angina. [21][22][23] In addition, IL-6 levels also reflect the degree of vascular inflammation and the severity of CAD. Mokhtar et al found significant increase in serum level of IL-6 in MVD and SVD patients as compared with non-CAD patients, a finding seen in our patients too.…”
Section: Discussionmentioning
confidence: 99%
“…20 This finding was consistent with those of Sarrafzadegan et al, Tang et al and Caselli et al who too had reported higher concentrations of IL-6 in patients with stable angina. [21][22][23] In addition, IL-6 levels also reflect the degree of vascular inflammation and the severity of CAD. Mokhtar et al found significant increase in serum level of IL-6 in MVD and SVD patients as compared with non-CAD patients, a finding seen in our patients too.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between IL-6 and ACS is not consistent across other studies. One study showed that IL-6 levels in patients with unstable angina were significantly higher than those in patients with ACS (102.4 ± 1.9 vs 224.6 ± 3.6, P = 0.007) (Sarrafzadegan et al, 2012). Therefore, the relationship between IL-6 and ACS needs further clarification.…”
Section: Introductionmentioning
confidence: 99%